Hieracium barrelieri, a new hawkweed species from S Italy, with notes on Tenore’s Hieracium murorum var. barrelieri (Asteraceae) - Gottschlich, Günter; Raimondo, Francesco Maria; Greuter, Werner; Di Gristina, Emilio (Phytotaxa, 2015)
A new species from Montevergine in Campania, Hieracium barrelieri, is described in detail. It is closest to H. acanthodontoides of . H. murorum var. barrelieri, an obsolete taxon described by Tenore, is also discussed, as it was partly based on the same population.